Optimisation of LEACH protocol based on a game theory clustering approach for wireless sensor networks - Yassine Oukessou; Mohamed Baslam; Mohamed Oukessou (Indonesian Journal of Electrical Engineering and Computer Science, 2021)
The wireless sensor network clustering routing mechanism is the best multi-hop algorithm used to aggregate data from sensors to the base station. Therefore the elected nodes refuse to be a clusters heads CH and have a selfish and non cooperative behaviours in each group cluster. All that due to the high electric energy consumption, and especially that the most existing sensors are powered by batteries. In this paper, we will analyse the selfishness behaviour by using the most knowing mathematical model Game theory to improve the interaction decision making for the CH selection, and make a comparison with LEACH protocol.